Effect of Ultrasonic Treatment in the Static and Dynamic Mechanical Behavior of AZ91D Mg Alloy - Helder Puga (Metals, 2015)
The present study evaluates the effect of high-intensity ultrasound (US) in the static and dynamic mechanical behavior of AZ91D by microstructural modification. The characterization of samples revealed that US treatment promoted the refinement of dendrite cell size, reduced the thickness, and changed the β-Mg17Al12 intermetallic phase to a globular shape, promoted its uniform distribution along the grain boundaries and reduced the level of porosity. In addition to microstructure refinement, US treatment improved the alloy mechanical properties, namely the ultimate tensile strength (40.7%) and extension (150%) by comparison with values obtained for castings produced without US vibration. Moreover, it is suggested that the internal friction, enhanced by the reduction of grain size, is compensated by the homogenization of the secondary phase and reduction of porosity. It seems that by the use of US treatment, it is possible to enhance static mechanical properties without compromising the damping properties in AZ91D alloys.